Impact of fairness concern on retailer-dominated supply chain. (January 2020) - Pan, Kewen; Cui, Zhibo; Xing, Axun; Lu, Qihui
Abstract: This study investigates the impact of fairness concern on a supply chain with a dominant retailer and two manufacturers on the basis of a two-echelon supply chain model. Through mathematical analysis and numerical study, this work examines the effects of fairness concern coefficient on the pricing, profitability, and utility of supply chain members. Results indicate that in the peer-induced fairness concern scenario, the profits of the two manufacturers decrease with the peer-induced fairness concern coefficient, whereas the profit of the retailer increases with the same coefficient. The utility of the cost-advantaged manufacturer increases, whereas that of others decreases. In the distributional fairness concern scenario, the profits of the two manufacturers and the retailer decrease with the distributional fairness concern coefficient, whereas the utility of the retailer increases with the same coefficient. The peer-induced and distributional fairness concern scenario leads to the property change of the two manufacturers and the retailer showing similar results with the two scenarios mentioned. Moreover, the supply chain profit increases with peer-induced fairness concern coefficient, but decreases with distributional fairness concern coefficient. In conclusion, peer-induced fairness concern scenario is the best scenario for the retailer, whereas no fairness concern on either side is preferred for the two manufacturers. Furthermore, the entire supply chain can gain additional profit from the distributional fairness concern scenario.